2020
DOI: 10.1371/journal.pone.0227581
|View full text |Cite
|
Sign up to set email alerts
|

Acute high-intensity and moderate-intensity interval exercise do not change corticospinal excitability in low fit, young adults

Abstract: Previous research has demonstrated a lack of neuroplasticity induced by acute exercise in low fit individuals, but the influence of exercise intensity is unclear. In the present study, we assessed the effect of acute high-intensity (HI) or moderate-intensity (MOD) interval exercise on neuroplasticity in individuals with low fitness, as determined by a peak oxygen uptake (VO 2peak ) test (n = 19). Transcranial magnetic stimulation (TMS) was used to assess corticospinal excitability via area under the motor evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Previous work showed that an acute bout of exercise increases corticospinal excitability in the nonexercised upper limb muscle of physically active young adults, whereas this increase was not observed in young adults that reported low levels of physical activity (10), which was confirmed in a study with separate groups of physically active young females and males (14). Similarly, other work showed that both moderate-intensity and HIIT acute exercise did not increase corticospinal excitability in sedentary young adults (18). Although the direct connection between modulation of corticospinal excitability and brainderived neurotropic factor (BDNF) has not been established, there is evidence that BDNF is a mediator of neuroplasticity (42).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous work showed that an acute bout of exercise increases corticospinal excitability in the nonexercised upper limb muscle of physically active young adults, whereas this increase was not observed in young adults that reported low levels of physical activity (10), which was confirmed in a study with separate groups of physically active young females and males (14). Similarly, other work showed that both moderate-intensity and HIIT acute exercise did not increase corticospinal excitability in sedentary young adults (18). Although the direct connection between modulation of corticospinal excitability and brainderived neurotropic factor (BDNF) has not been established, there is evidence that BDNF is a mediator of neuroplasticity (42).…”
Section: Discussionmentioning
confidence: 69%
“…Specifically, it was hypothesized that HIIT would decrease intracortical inhibition and transcallosal inhibition as well as increase ICF in M1 (3,4,9,11,17). It was expected that corticospinal excitability would be unaffected by acute HIIT, as shown by the majority of previous studies in young adults (1,3,4,7,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed an acute bout of high-intensity cycling resulted in increased excitability, reduced inhibition, and improved motor performance in a ballistic thumb task; however, the activity levels of participants were not reported ( Opie and Semmler, 2019 ). No increase in corticospinal excitability was reported following either high or moderate intensity exercise in low-fit individuals ( El-Sayes et al, 2020 ); however, inhibitory measures were significantly reduced following both high ( Stavrinos and Coxon, 2017 ) and moderate intensity cycling protocols ( Singh et al, 2014 ; Smith et al, 2014 ), where participants were either sedentary or of unknown fitness status.…”
Section: Introductionmentioning
confidence: 95%
“…But the effect was inconsistent and heterogenous, with 61% of the studies reporting no significant change in BDNF after aerobic exercise 24 . Considerable variability in exercise-induced changes in CSE has also been observed in both sedentary 23 , 39 and active individuals 23 , with a spread of individuals showing increases, decreases, and no changes in CSE after aerobic exercise. Further investigation of such biomarkers may be helpful to understand exercise effects on motor learning.…”
Section: Discussionmentioning
confidence: 96%